Evolution in sentinel lymph node biopsy in breast cancer. (March 2018) - Qiu, Si-Qi; Zhang, Guo-Jun; Jansen, Liesbeth; de Vries, Jakob; Schröder, Carolien P.; de Vries, Elisabeth G.E.; van Dam, Gooitzen M.
Abstract: Sentinel lymph node biopsy (SLNB) is the standard of care for axillary staging in clinically node-negative (cN0) breast cancer patients without neoadjuvant chemotherapy (NAC). The application of SLNB in patients receiving NAC has also been explored. Evidence supports its use after NAC in pretreatment cN0 patients. Nonetheless, its routine use in all the pretreatment node-positive patients who become cN0 after NAC is unjustified due to the unacceptably high false-negative rate, which can be improved in a subset of patients. Axillary surgery omission in selected patients with a low risk of ALN metastasis has gained more and more research interest because the SLNs are tumor-free in more than 70% of all patients. To avoid drawbacks of conventional mapping methods, novel techniques for SLN detection have been developed and shown to be highly accurate in patients with early breast cancer. This article reviews the progress in SLNB in patients with breast cancer.